Pengembangan Desain Instruksional Model Project Based Learning Terintegrasi Keterampilan Proses Sains Untuk Meningkatkan Literasi Sains - Nuraini Nuraini; Edy Waluyo* (Universitas Syiah Kuala, 2021)
Facing today's 21st century learning, teachers need to foster science literacy and consider learning strategies that suit the conditions and potential of students whose learning processes focus on providing firsthand experience and applying science knowledge. Literacy skills are fundamental things that students must do in facing the global era to be able to meet the needs of life in various situations. This research aims to develop instructional design through project learning based on science process skills to improve valid, practical and effective literacy skills. This research uses a type of research on Borg and Gall model development which is a systemic process that starts from the analysis of needs, product design, product development, implementation and evaluation of products. The subjects in the research were students in grade VII SMPN 1 Selong and Madrasah Tsanawiyah Muallimat NW Pancor numbered 64 people. Data collection uses validation sheets, practicality guidelines, and tests to measure students' science literacy skills. Data is analyzed with descriptive analysis techniques. The results of the analysis showed that the instructional design of the project based learning model based on science process skills fall into the category of valid, practical and effective and feasible to use. The products developed also have a potential effect in improving students' science literacy skills indicated by an N-Gain score of 0.77 with a high category